2020
DOI: 10.1139/apnm-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Iron status is associated with worker productivity, independent of physical effort in Indian tea estate workers

Abstract: Iron deficiency (ID) is the most common nutrient deficiency in the world, affecting roughly 40% of women in non-industrialized countries. Iron is the essential element in hemoglobin, the major carrier of blood oxygen and oxidative metabolism that supports physical and cognitive performance. The relationship between iron and physical work capacity suggests that iron deficient individuals could experience reduced work output. Participants were 138 experienced tea pluckers aged 18-55 years from the Panighatta Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Hasil penelitian pada pekerja di Indonesia menunjukkan anemia cukup tinggi terutama pada pekerja perempuan. Anemia dapat menurunkan produktivitas tenaga kerja, menghambat keberlangsungan kegiatan usaha dan tentunya mempengaruhi pembangunan ekonomi dan kesejahteraan masyarakat (Blakstad et al, 2020). Marice ( 2009) melaporkan bahwa diantara 943 pekerja, tingkat anemia anemia pada pekerja lakilaki sejumlah 5.6% (36 orang) dan pekerja perempuan 32.1% (97 orang).…”
Section: Pembahasanunclassified
“…Hasil penelitian pada pekerja di Indonesia menunjukkan anemia cukup tinggi terutama pada pekerja perempuan. Anemia dapat menurunkan produktivitas tenaga kerja, menghambat keberlangsungan kegiatan usaha dan tentunya mempengaruhi pembangunan ekonomi dan kesejahteraan masyarakat (Blakstad et al, 2020). Marice ( 2009) melaporkan bahwa diantara 943 pekerja, tingkat anemia anemia pada pekerja lakilaki sejumlah 5.6% (36 orang) dan pekerja perempuan 32.1% (97 orang).…”
Section: Pembahasanunclassified
“…Namely, authors found that an increase of 1.0 g/L in Hb concentration predicted 0.71 kg (3.3%) more tea plucked over 3 hours, providing additional affirmative evidence to support our own conclusions. 21…”
Section: Discussionmentioning
confidence: 99%
“…Namely, authors found that an increase of 1.0 g/L in Hb concentration predicted 0.71 kg (3.3%) more tea plucked over 3 hours, providing additional affirmative evidence to support our own conclusions. 21 Interestingly, strong positive associations were also found between Hb levels and the quantity of active work time, assessed directly or as a function of worker absenteeism. This suggests that anemia may not only result in greater worker fatigue but may also be implicated in more severe comorbidities which can interfere with one's ability to attend work regularly-a potential representation of the far-reaching consequences of anemia for employee health.…”
Section: Duration Of Iron Interventionmentioning
confidence: 95%
“…In adults, iron deficiency leads to reduced physical capacity and productivity (Blakstad et al., 2020 ). Severe anemia is responsible for 20% of maternal deaths (Teshome et al., 2020 ) and increases the risk of fetal morbidity and mortality, as well as prematurity and low birth weight (Rocha et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%